ATRT-05. USING DROSOPHILA TO EXPLORE THE FUNCTIONAL RELEVANCE OF GENES AFFECTED BY EPIGENETIC ALTERATIONS IN ATYPICAL TERATOID/RHABDOID TUMORS (AT/RT). Issue 2 (22nd June 2018) - Tegeder, Isabel; Thiel, Katharina; Berlandi, Johannes; Johann, Pascal; Erkek, Serap; Kool, Marcel; Jeibmann, Astrid; Hasselblatt, Martin
Abstract: Atypical teratoid/rhabdoid tumors (AT/RT) are highly malignant brain tumors arising in young children. The majority of AT/RT is characterized by inactivation of one single gene, the chromatin remodeling complex member SMARCB1 (INI1/hSNF5). However, AT/RTs are epigenetically heterogeneous and can be divided into molecular subgroups based on gene expression, DNA methylation profiles and enhancer landscapes (H3K27ac). Biostatistical analysis of ChIP-seq data resulted in a large set of genes predicted to be affected by differential histone modifications, but little is known on the functional role of these genes in the detrimental effects of SMARCB1 deficiency. We thus explored the functional relevance of 1083 candidate genes using shRNA modifier screens in a Drosophila melanogaster model of SMARCB1 deficiency in vivo. The lethal phenotype caused by glial-specific knockdown of Snr1, the fly orthologue of SMARCB1 was shifted to later stages of development upon additional knockdown of 89 out of 1083 candidate genes. These included CG10348, the fly orthologue of transcriptional regulator PRDM16. We found PRDM16 to be highly expressed in AT/RT. Knockdown of PRDM16 in SMARCB1-deficient rhabdoid tumor cells caused a significant reduction in cell viability. These results demonstrate that fly models can be employed for the identification of functionally relevant genes in the biology of AT/RT. Supported by IZKF Münster (Ha3/019/15).